Universally autonomous self-healing elastomer with high stretchability - Guo, Hongshuang (Nat Commun, 2020)
Developing autonomous self-healing materials for applications in harsh conditions is challenging because the reconstruction of interaction in material for self-healing will experience significant resistance and fail. Herein, a universally self-healing and highly stretchable supramolecular elastomer is designed by synergistically incorporating multi-strength H-bonds and disulfide metathesis in polydimethylsiloxane polymers. The resultant elastomer exhibits high stretchability for both unnotched (14000%) and notched (1300%) samples. It achieves fast autonomous self-healing under universal conditions, including at room temperature (10 min for healing), ultralow temperature (−40 °C), underwater (93% healing efficiency), supercooled high-concentrated saltwater (30% NaCl solution at −10 °C, 89% efficiency), and strong acid/alkali environment (pH = 0 or 14, 88% or 84% efficiency). These properties are attributable to synergistic interaction of the dynamic strong and weak H-bonds and stronger disulfide bonds. A self-healing and stretchable conducting device built with the developed elastomer is demonstrated, thereby providing a direction for future e-skin applications.